PATTERN RECOGNITION METHODS FOR BUILDING A NETWORK DIAGNOSTIC SYSTEM - V. G. Rodchenko; E. V. Olizarovich; A. I. Zhukevich (Informatika)
A generic method for computer networks diagnosis is proposed, which is based on thetheory of pattern recognition. We suggest to model the network status on the basis of the observed traffic's characteristics. Implementation mechanisms of all diagnostic stages are considered. They include formation of the dictionaries and performing procedures of training and classification.